Magyarországi diákok egyetemjárása az úkorban 1–22.: (Könyvbemutató és recenzió) - P. Szabó, Béla (Gerundium, 2016)
THE UNIVERSITY ATTENDANCE OF STUDENTS FROM HUNGARY IN THE MODERN AGE, 1–22 (BOOK PRESENTATION AND REVIEW). In this generically peculiar sort of writing, which is ACTUALLY a book review that grew out of the observations at an actual book presentation, is the introduction of an enterprise which is unique even by European standards. It is a series of books that has been in the making for twenty years under the leadership of Professor László Szögi. he primary objective of the project is to inventorize all those students in Hungary who – between the beginning of the 16th century and the beginning of the 20th century – pursued advanced studies abroad at some European university. he overview evaluates the unique volume of the enterprise, appreciates, without attempting to be complete, its most spectacular merits, outlines the possibilities of the utilization of the amassed data, and highlights, through personal experience, why this unique low of books is so signiicant to the scholars of several areas of knowledge.